Structural Equation Modeling to Evaluate the Effect of Body Shape Concern and Body Appreciation on Eating Behavior Pattern among University Students - Maryam KHEIROLLAHPOUR; Mahmoud DANAEE; Amir Feisal MERICAN; Asma Ahmad SHARIFF (Tehran University of Medical Sciences, 2020)
No Abstract